2006
DOI: 10.1063/1.2399393
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen induced strong green light emission from low-temperature grown amorphous silicon nitride films

Abstract: Luminescent amorphous silicon nitride films were fabricated by plasma-enhanced chemical vapor deposition at room temperature followed by thermal oxidation at 100°C. Very bright green emissions were clearly observed with the naked eye in a bright room after the samples had been oxidized. The emission peak is located at 495nm. Fourier-transform infrared absorption spectra and results of depth profiling with x-ray photoelectron spectroscopy indicate that the introduction of oxygen is of a key role in enhancing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
35
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 24 publications
1
35
0
Order By: Relevance
“…Intrinsic emission has been also observed in SRN ilms [27][28][29][30][31]. For example, an orange emission at 600 nm was observed at room temperature and has been related to the electron-hole pairs' recombination within Si-nps [27].…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…Intrinsic emission has been also observed in SRN ilms [27][28][29][30][31]. For example, an orange emission at 600 nm was observed at room temperature and has been related to the electron-hole pairs' recombination within Si-nps [27].…”
Section: Introductionmentioning
confidence: 74%
“…For example, an orange emission at 600 nm was observed at room temperature and has been related to the electron-hole pairs' recombination within Si-nps [27]. Also, green emission has been observed in nitrogenrich silicon nitride, which was atributed to radiative recombination in localized states related to Si-O [28]. Some other authors have shown signiicant improvement of the green emission intensity using oxidized silicon-rich nitride [29].…”
Section: Introductionmentioning
confidence: 83%
“…However, the luminescence can be only observed in the samples annealed at high temperatures greater than 850 °C. In our previous work, we reported oxygen-induced strong green PL of its peak around 500 nm from a-SiN x O y film prepared at room temperature [17]. LED with MIS structure of Al/a-SiN x O y /ITO was successfully fabricated and emitted the intense uniform green-yellow light [18].…”
Section: Introductionmentioning
confidence: 98%
“…In the past decade, luminescent Si-based materials have aroused great research interests owing to their potential application in Si-based monolithic optoelectronic integrated circuits [1][2][3][4][5][6][7][8][9][10][11][12][13]. Since bulk silicon is a poor light emitter due to its indirect band gap that requires phonons for momentum conservation, a tremendous amount of research has been devoted to Si nanostructure embedded in different dielectric matrices such as silicon oxide (SiO x ), silicon nitride (SiN x ) and silicon oxynitride (SiN x O y ) [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Since bulk silicon is a poor light emitter due to its indirect band gap that requires phonons for momentum conservation, a tremendous amount of research has been devoted to Si nanostructure embedded in different dielectric matrices such as silicon oxide (SiO x ), silicon nitride (SiN x ) and silicon oxynitride (SiN x O y ) [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. Although research in these system has made great progress, unfortunately, there is still a long way towards the realization of practical application.…”
Section: Introductionmentioning
confidence: 99%